Collaborative Institutional Training Initiative (CITI): Student Experience - Lillian Nguyen; Mark Hirsch (University Library System, University of Pittsburgh, 2024)
CITI Training (Collaborative Institutional Training Initiative) provides bioethical research training for investigators around the globe. We report a pilot case study on the user experience (thoughts, feelings) of completing mandatory CITI Training from the perspective of a rising high-school sophomore and a medical student with limited research knowledge. These experiences were compared via reflections after completing both CITI Trainings. The study results highlighted the obstacles experienced by a naïve researcher while completing CITI Training. We argue that CITI Training ought to make accommodations to ensure content is understandable to highschool and medical students with limited research knowledge.